Developing Student's Speaking Competence Through Storytelling at the Second Grade Student's of SMK Negeri 1 Magelang in Academic Year 2013 / 2014 - Septanti, Rina Dewi; Ghozali , Imam; Robiasih, Hasti (UPA Bahasa Universitas Tidar And HISKI Kedu, 2021)
This research is aimed to describe the development of a model of teaching speaking competence called Storytelling, a model of teaching English to enhance the students’ speaking competence. Further, the research also reveals the strengths and limitations of aims at Storytelling activity in SMK Negeri 1 Magelang. This research belongs to an educational research and development (or called R & D). The model was developed adapting Borg and Gall’s Model (1983) simplified into six steps. The steps are (1) Theories and Studies related to Storytelling Technique or Product Analysis, (2) Planning and Preparation for doing Storytelling Technique, (3) Expert Validation and Revision Related to Storytelling Technique , (4) Developing Storytelling Technique in class, (5) Revision of Product , and (6) Final Product . The field tryout was conducted in one class of grade XI students of SMK Negeri 1 Magelang . The instruments used in this research were classroom observation sheet, students’ opened-questionnaire sheet and questions of students’ interview. The collecting data in this research were analyzed by using qualitative and analysis from Miles and Huberman (1994) consisting of four steps of collecting data, reducing data, displaying data, and verifying conclusions. Findings show that Storytelling as a model of teaching speaking shows some strengths; in development stage students’ speaking competence, students’ willingness to voluntary tell their experience in front of the class, the class’ participation in asking questions to the presenters, their willingness to attend the storytelling activity patiently, and also their disappointment due to not being given a chance to perform in front of the class get improvement. Furthermore, Storytelling is a meaningful activity which gives some benefits to the students such as developing feeling of self confidence and braveness and providing more chance to speak that can develop students’ speaking competence.